Idle Time Analysis of Construction Equipment Using Digital Image Processing - Ushadevi , Patil; Patil , S. A.; Zope , Rupali (Research and Developments in Engineering Research Vol. 5, 2023)
This chapter investigates image analysis to quickly identify changes during excavation activities. Correct analysis of construction equipment idle time is critical for the cost-effective energy use of construction equipment in large projects. Higher output may be achieved with reduced idle time of equipment; nonetheless, this is optimal time according to human observation. This work describes an image-processing-based system for automatically determining the idle time of hydraulic excavation. HSV is used in the tracing process and picture segmentation. The HSV colour space is more useful than the RGB colour scheme for specifying and tracking construction equipment. The results of the experiments show that the offered technique provides significantly more effective equipment management in the construction business.